X-Press: Two-Stage X-Tolerant Compactor With Programmable Selector - Rajski, J.; Tyszer, J.; Mrugalski, G.; Wu-Tung Cheng; Mukherjee, N.; Kassab, M. (IEEE transactions on computer-aided design of integrated circuits and systems, 2008)
This paper presents X-Press - a new two-stage test-response compactor that can be easily integrated with a multiple scan-chain environment. This compactor preserves all benefits of spatial compaction and offers, due to its overdrive sequential section, compression much higher than the ratio of scan chains to compactor outputs. X-Press is also capable of handling a wide range of unknown (X) state profiles by deploying a two-level scan-chain-selection mechanism. In addition to a new compactor architecture, original contributions of this paper include a detailed analysis of two-level error masking caused by X states and a new algorithm to both rank scan chains and then to determine, in per-pattern mode, scan-chain-selection rules used to suppress X states. Experimental results obtained for a variety of designs show feasibility and efficiency of the proposed compaction scheme, altogether with actual impact of X states on a test-pattern count. Finally, diagnostic capabilities of the proposed scheme accompanied by further experimental results are also analyzed.